Landscape Linguistic of Sumenep Tourism Destination in the New Normal Era - Putri Nur Diana; Tazkiyatul Wildaniyah; Tiara Agil Tri Oktavia; Rosyida Ekawati (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2022)
This study examines linguistic landscape perspective of language used in labeling historical objects at the Keraton Sumenep Museum. Keraton Sumenep Museum is a place to collect, treat, present and preserve the historical objects of the Sumenep Palace and one of the tourism destination in Sumenep. It employed a qualitative method to describe and explain the languages displayed, the sign meterials, and the sign categories in the museum following the taxonomy signs by Spolsky and Cooper. The applied method has assisted the researchers to reach the objectives of this study by getting 124 pictures of landscape linguistic signs. The result of this research shows that linguistic landscape in the museum buildings consist of monolingual and bilingual in Indonesian and English language. The Indonesian language is being chosen because most of the visitors are from locals who can communicate in Indonesian. Moreover, English language is displayed in LL because there are a number of international tourists who come to visit the museum.